The Role of Job Authority and Employee Empowerment on Employee Commitment in the Public Service Sector - Djunaedi, Djunaedi; Kusnadi, Iwan Henri; Apramilda, Riesna; Osman, Isnawati; Setyawati, Kiki; Handayani, Sri (Malikussaleh University, Aceh, Indonesia, 2025)
Team member commitment is at the core of organizational performance and durability, especially in the public sector. The study seeks to supplement existing knowledge by examining the effects of job authority and job empowerment on team member commitment and its impact on motivation, job satisfaction, and loyalty to the organization. This was obtained through a mixed-method approach, drawing together quantitative survey data with qualitative in-depth interviews with public workers. The findings indicate that the greater the level of authority, the more responsibility there is, and the more freedom there is for decision-making, the greater the commitment to the organization. Knowing how to do the work properly and having the proper skills and self-confidence were also essential for team member commitment. Employees at the lower organizational levels reported having feelings of encouragement and interest in the company, as well as integration into the strategic objectives of the company or enterprise. These results indicate the need for public service organisations to adopt a sustainable employee commitment culture focusing on authority and empowerment. Such issues need to be examined as time passes in future studies. The findings emphasize the importance of job authority and empowerment as determinants of team member engagement in the public sector compared to team member engagement in the private sector: assistive medical devices and many other organizations.